One-step Method to Fabricate Poly(ethylene terephthalate)/Gd(OH)3 Magnetic Nanofibers Towards MRI-active Materials with High T1 Relaxivity and Long-term Visibility. (December 2022) - Jia, Yifan; Yuan, Weiwen; Xu, Mengmeng; Yang, Congyi; Chen, Lei; Wang, Shuo; Topham, Paul D.; Luo, Guoxuan; Wang, Mo; Zhang, Yong; Jiang, Guihua; Yu, Qianqian; et al.
Highlights: Sub-nanoscale Gd(OH)3 was in-situ synthesized within PET fibers via one-step electrospinning and showed 34 times higher T1 relaxivity than that of aggregates. Only 0.32 wt.% Gd dosage was loaded in the composite fibers which can achieve similar MRI contrast of commercial injectable agent. Approximate 139 days in vivo MRI T1 positive contrast is promising for future biomedical applications Abstract: Magnetic resonance imaging (MRI)-active polymers exhibit unique advantages for in vivo diagnosis. Here, in order to endow electrospun fibers with long-term T1 positive MRI visibility, MRI contrast agent (CA), Gd(OH)3, is introduced in a new, extremely convenient method. Crucially, GdCl3 is reacted with NaOH in situ during electrospinning, with flexibility to deliver both well-dispersed and aggregated Gd(OH)3 clusters within a poly(ethylene terephthalate) (PET) matrix. T1 and T2 relaxivities of Gd(OH)3 in PET nanofibers are studied. Well-dispersed Gd(OH)3 (sub-nanometer in size) exhibits 34 times higher T1 relaxivity than aggregated nanoparticles when embedded within the fibers. The morphology, structure, magnetic properties, tensile properties, imaging performance and biosafety of the PET/Gd(OH)3 composite fibers are evaluated to identify the optimum conditions to produce new materials with balanced properties, excellent in vivo positive contrast and approximately 139 days imaging lifetime. Comparing this sample with a commercial CA, only 0.32 wt.% Gd loading is needed to attain similar MRI signal intensity. In summary, PET/Gd(OH)3 long-term MRI-active fibers show great potential for future biomedical applications and the study also provides a promising new general strategy to enhance the MRI T1 positive contrast of electrospun fibers of a whole host of other systems. Graphical Abstract: Image, graphical abstract